Chronic Binge Alcohol Administration Accentuates Expression of Pro‐Fibrotic and Inflammatory Genes in the Skeletal Muscle of Simian Immunodeficiency Virus–Infected Macaques. (November 2014) - Dodd, Tracy; Simon, Liz; LeCapitaine, Nicole J.; Zabaleta, Jovanny; Mussell, Jason; Berner, Paul; Ford, Stephen; Dufour, Jason; Bagby, Gregory J.; Nelson, Steve; Molina, Patricia E.
<x xml:space="preserve">Abstract</x> Background Chronic binge alcohol (CBA) administration exacerbates skeletal muscle (SKM) wasting at the terminal stage of simian immunodeficiency virus (SIV) infection in rhesus macaques. This is associated with a pro‐inflammatory and oxidative milieu which we have previously shown to be associated with a disrupted balance between anabolic and catabolic mechanisms. In this study, we attempted to characterize the SKM gene expression signature in CBA‐administered SIV‐infected macaques, using the same animals from the previous study. Methods Administration of intragastric alcohol or sucrose to male rhesus macaques began 3 months prior to SIV infection and continued throughout the duration of study. Gene transcriptomes of SKM excised at necropsy ( 10 months post‐SIV) from healthy nacontrol (Control), sucrose‐administered, SIV‐infected (SUC‐SIV), and CBA‐administered, SIV‐infected (CBA‐SIV) macaques were evaluated in microarray data sets. The Protein Analysis Through Evolutionary Relationships classification tool was used to filter differentially regulated genes based on their predicted function into select biological processes relevant to SKM wasting which were inflammation, extracellular matrix (ECM) remodeling, and metabolism. Results In total, 1, 124 genes were differentially regulated between SUC‐SIV and Controls, 2, 022 genes were differentially expressed between the CBA‐SIV and Controls, and 836 genes were differentially expressed between CBA‐SIV and SUC‐SIV animals. The relevance of altered gene expression was reflected in the up‐regulation of pro‐inflammatory CCL‐2, CCL‐8, CX3CL1, SELE, HP, and TNFRS10A mRNA expression. In addition, ECM remodeling was reflected in the up‐regulation of TIMP‐1, MMP 2, and MMP 9 mRNA expression and transforming growth factor‐beta 1 protein expression. In addition, hydroxyproline content and picrosirius staining reflected increased collagen deposition in the CBA‐SIV muscle tissue. Conclusions The results of the study demonstrate SKM inflammation as an important underlying mechanism for muscle wasting. In addition, the study provides evidence of SKM fibrotic transformation as a factor in CBA‐induced accentuation of SIV‐associated muscle wasting.